The efficacy of neuroendoscopic surgery treating patients with thalamic hemorrhage accompanied by intraventricular hematoma - Yang, Feilong; Xu, Wuhuan; Tang, Xielin; Yang, Yan; Ku, Buqian A.; Zhang, Yiping; Yang, Xiaoli; Xie, Wei; Hui, Xuhui (Frontiers in Surgery, 2024)
ObjectiveNeuroendoscopic surgery (NES) has been proven to be safe and effective in hematoma evacuation for cerebral hemorrhage. However, its efficacy for thalamic hemorrhage accompanied by intraventricular hematoma (THAVH) remains unclear. The aim of this study is to determine the efficacy of NES in treating THAVH.MethodA retrospective study was carried out. The data of patients diagnosed with THAVH were collected from January 1st, 2019, to January 1st, 2022. Patients received the NES or external ventricle drainage (EVD) treatment were assigned to the NES or EVD group, respectively. As primary outcomes, the hematoma evacuation volume, residual hematoma volume, and hematoma clearance rate were separately calculated based on the hematoma site; and the 180-day-mRS score was assessed. As secondary outcomes, the length of stay in the ICU and hospital, and the adverse events were also compared.ResultsThirty-five patients, aged 66.37 ± 6.62 years, were in the NES group; and 40 patients, aged 68.75 ± 7.22 years, were in the EVD group. The baseline characteristics in the two groups were similar (P > 0.05). The gross hematoma evacuation volume, volume of hematoma evacuated in the thalamus or the ventricle, and the hematoma clearance rate were greater in the NES group than in the EVD group on the 1st day after surgery (P < 0.05). The patients had a better rank of mRS in the NES group (P < 0.05). Compared with patients with mRS > 3, the mean residual hematoma volume in the thalamus of patients with mRS ≤3 on the 1st and 7th day were less in each group (P < 0.05), respectively. A residual hematoma volume in the ventricle of patients with mRS ≤3 was less than that of patients with mRS >3 in the EVD group on the 1st day after surgery (P < 0.05). GCS score on the 3rd day was greater in the NES group (P < 0.05). The incidence of lung infection was lower in the NES group (P < 0.05). The length of stay in the ICU and hospitalization duration were shorter in the NES group (P < 0.05).ConclusionsNeuroendoscopic surgery has a greater hematoma clearance rate, a lower lung infection rate and a shorter duration in the hospital. Neuroendoscopic surgery might improve patients’ prognosis. Neuroendoscopic surgery is a safe and effective procedure for treating thalamic hemorrhage accompanied by intraventricular hematoma.